AD Hoc Mobile Wireless Networks : Protocols and Systems - Toh, C.-K. (Chennai, India Pearson Education, 2016)
Covering routing, the most significant difference between Ad Hoc networks and base station networks, this text explores in detail new routing protocols for Ad Hoc networks, such as Associativity Based routing (ABR) and other IETF MANET protocols. It also discusses implementation issues and presents prototype implementation
Include Reference and Index
Keywords: Wireless communication systems -- Ad hoc networks (Computer networks)